PEMINAT APLIKASI BLIBLI.COM DENGAN MENGGUNAKAN MODEL UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) - Resti Anindya Putri; Helni Mutiarsih Jumhur (Faculty of Economic and Business, University of Pasundan, 2019)
The purpose of this study to determine the effect of variables Performance Expectancy, Effort Expectancy, Trust, and Social Influence to Behavioral Intention. In addition to know the influence of Performance Expectancy and Effort Expectancy to Trust mobile application Users in Blibli.com and to know the effect of Facilitating Conditions and Behavioral Intention towards Use in Blibli.com application Users. Data collection was performed on Blibli.com application users across Indonesia with 300 respondents by using purposive sampling method, and analyzed by structural equation model (SEM). Performance Expectancy has significant effect to Trust, Social Influence significant to Behavioral Intention, and Behavioral Intention Significant towards Use. The variable that does not affect is the Effort Expectancy towards Trust, Effort Expectancy and Trust to Behavioral Intention, and Facilitating Conditionss against Use. This research is expected to be Useful for PT Global Digital Niaga (GDN) in order to achieve the increasing interest of Blibli.com application Users.